#### Answer

$\dfrac{1}{16}$

#### Work Step by Step

$(-64)^{-(2/3)}=\dfrac{1}{(-64)^{2/3}}=\dfrac{1}{\sqrt[3] {(-64)^{2}}}=\dfrac{1}{\sqrt[3] {4096}}=\dfrac{1}{16}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\dfrac{1}{16}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.